2009
DOI: 10.1089/jwh.2008.1160
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Use, and Concerns about Contraceptive Methods among Sero-Discordant Couples in Rwanda and Zambia

Abstract: Objective: The unique needs of sero-discordant couples are largely missing from many current family planning efforts, which focus on the prevention of pregnancies in absence of the reduction of the risk of human immunodeficiency virus (HIV) and other sexually transmitted infections (STIs). Conversely, HIV testing and programs focus exclusively on condom use without discussion of more effective contraceptive methods. In order to provide information to inform the development of family planning services tailored … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
59
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(62 citation statements)
references
References 27 publications
(21 reference statements)
3
59
0
Order By: Relevance
“…Previous research with the same cohort of couples showed a high level of health concerns around contraceptive methods, with the highest percentage of men and women reporting concerns about OCPs compared with injectables, Norplant, or IUD. 11 In particular, previous work has demonstrated that men in this cohort report more concerns about IUDs than women and that the IUD was the method both men and women were most likely to report would fail to prevent pregnancy. This may explain the low levels of IUD uptake after the interventions.…”
Section: Stephenson Et Almentioning
confidence: 72%
See 2 more Smart Citations
“…Previous research with the same cohort of couples showed a high level of health concerns around contraceptive methods, with the highest percentage of men and women reporting concerns about OCPs compared with injectables, Norplant, or IUD. 11 In particular, previous work has demonstrated that men in this cohort report more concerns about IUDs than women and that the IUD was the method both men and women were most likely to report would fail to prevent pregnancy. This may explain the low levels of IUD uptake after the interventions.…”
Section: Stephenson Et Almentioning
confidence: 72%
“…This may explain the low levels of IUD uptake after the interventions. 11 It is important that efforts to provide family planning services to couples affected by HIV incorporate information on the efficacy, likely side effects, and impact on health of contraceptive methods and take steps to tackle any misconceptions that may surround contraception. Although such misinformation is likely present in the general reproductive-age population, it is plausible to suggest that those affected by HIV may have more concerns about contraceptive use linked to perceptions of their own health status.…”
Section: Stephenson Et Almentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, serodiscordant relationships among primary partners have increasingly become identified as a key context for the transmission of HIV globally [Jin et al 2007, Dunkle et al 2008, Eaton et al 2009, Hernando et al 2009 In sub-Saharan Africa, it is estimated that the majority of new HIV infections now occur within married or cohabiting couples (Guthrie et al 2007, Desgrées-duLoû and Orne-Gliemann 2008, Beyeza-Kashesya et al 2009, Grabbe et al 2009). Research from various countries with different types of HIV epidemics (generalised, low-level, or concentrated) suggests that serodiscordant relationships are common.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have explored men’s role in reproductive health and suggest that partner involvement in FP could increase contraceptive uptake and use in SSA (Grabbe et al, 2009; Becker, 1996; Mbizvo & Bassett, 1996). With the importance of dual contraception method use in the HIV-positive population and the need for male acceptance of condom use, male partner involvement could also help prevent HIV transmission.…”
Section: Introductionmentioning
confidence: 99%